(untitled) (Indian Journal of Traditional Knowledge (IJTK), 2025)
Type 2 diabetes mellitus is one of the more prevalent long term metabolic disorders creating a formidable health hazard globally, especially in middle-aged women. This study evaluates the effectiveness of complementary holistic practices like the yoga and mud therapy on biochemical variables’ levels, such as glycated haemoglobin (HbA1c), fasting blood sugar (FBS), post prandial blood sugar (PPBS), and Triglyceride (TG) among the middle-aged women suffering with Type 2 Diabetes Mellitus of Chennai district. 90 subjects, aged between 45 to 55 years, were selected through randomized sampling and grouped into three, such as Group A (Yoga and Mud Therapy), Group B (Yoga) and Group C (Control Group), with 30 participants in each category. Group A had 1.5 h session per day, which includes 1 h of structured yoga program comprising Sukshma Vyayama, Surya Namaskar, Asanas, Pranayama, Dhyana and 30 min of Mud therapy and Group B had 1 h of structured yoga five days a week, for a time span of 12 weeks, wherein Group C were in active rest. Pre and post intervention biochemical variable levels were recorded to assess changes in glycemic control. Paired t-test and ANOVA were implemented to understand the changes of the glycemic levels. The results indicated a significant reduction in all biochemical variables level under consideration in Group A (p<0.001) in comparison to the other groups. The results imply that Yoga and Mud Therapy practiced regularly could benefit middle-aged women in the management of T2DM. A longer period of intervention could provide more confirmation on the effect of these practices on reducing levels of proposed biochemical variables.